A New Marine Species of Miracula (Oomycota) Parasitic to Minidiscus sp. in Icelandtitle. Issue 4 (4th July 2021) - Buaya, Anthony T.; Scholz, Bettina; Thines, Marco
Abstract: Obligate endoparasitic oomycetes are known to ubiquitously occur in marine and freshwater diatoms, but their diversity is still largely unexplored. Many of these parasitoids are members of the early-diverging oomycete lineages ( Miracula, Diatomophthora ), others are within the Leptomitales of the Saprolegniomycetes ( Ectrogella, Lagenisma ) and some have been described in the Peronosporomycetes ( Aphanomycopsis, Lagenidium ). Even though some species have been recently described and two new genera were introduced ( Miracula and Diatomophthora ), the phylogeny and taxonomy of most of these organisms remain unresolved. This is contrasted by the high number of sequences from unclassified species, as recently revealed from environmental sequencing, suggesting the presence of several undiscovered species. In this study, a new species of Miracula is reported from a marine centric diatom ( Minidiscus sp.) isolated from Skagaströnd harbor in Northwest Iceland. The morphology and life cycle traits of this novel oomycete parasite are described herein, and its taxonomic placement within the genus Miracula is confirmed by molecular phylogeny. As it cannot be assigned to any previously described species, it is introduced as Miracula islandica in this study. The genus Miracula thus contains three described holocarpic species ( M. helgolandica, M. islandica, M. moenusica ) to which likely additional species will need to be added in the future, considering the presence of several lineages known only from environmental sequencing that clustered within the Miracula clade.